EVALUATION OF RAINFALL TRENDS DUE TO CLIMATE CHANGE: A CASE STUDY OF SAMARU, ZARIA - Garuba, H. S.; Mukhtar, M. K.; Ugama, G. N.; Jamila, A.; Aliyu, M. K.; Yahaya, G. (FUDMA JOURNAL OF SCIENCES, 2022)
Rainfall is the major source of water for agricultural activities in Nigeria, but there has been a major variation due to climate change. This study is to assess the change in rainfall trend due the impact of climate change in Samaru, Zaria Kaduna State. Rainfall data from 1981 – 2018 (38 years) were collected from the Nigerian Meteorological Agency (NIMET). The data was analyzed using Excel and XL-Statistics to evaluate the mean, standard deviation and coefficient of variation of monthly and annual rainfall and other statistical parameter. The study revealed that there is a significant change in the trend of annual rainfall as the highest rainfall was recorded in year 1994 with a value of 1487 mm and lowest rainfall in 1999 as 440 mm. The highest average monthly rainfall data is between July to September and a peak rainfall in August with an average value of 547 mm. This analysis provide useful information to farmers which can be used a basis for planning annual crop planting and also water resources planning such as in irrigation scheduling.